Pengembangan Modul Pelatihan Akuntansi dan Pajak untuk UMKM Berbasis SAK EMKM - Vista Yulianti; Edi Triwibowo; Adinda Syafitri (Jurnal Pengabdian Masyarakat, 2026)
The community service activity entitled “Development of Accounting and Tax Training Modules for MSMEs Based on SAK EMKM” aims to improve financial literacy and tax compliance among Micro, Small, and Medium Enterprises (MSMEs). The low level of understanding among MSMEs regarding standardized financial recording and tax obligations remains a major challenge in achieving sustainable business management. Therefore, this program was designed using a participatory training method with a Participatory Training and Action Learning (PTAL) approach, which combines short lectures, hands-on practice, interactive discussions, and intensive mentoring. The activity was conducted at Universitas Pelita Bangsa, involving 12 MSME actors from Bekasi Regency as active participants. The results show a significant increase in participants’ understanding, from 55% before the training to 88% after the training. In addition to producing practical and easily applicable training modules, this activity also fostered the emergence of a digital accounting community and local leaders capable of acting as facilitators for other MSMEs. This program demonstrates that participatory and contextual training is effective in building accounting competencies, increasing tax awareness, and encouraging social transformation toward financial independence and accountability among MSMEs in a sustainable manner.